Synthesis ZrO2-Montmorillonite and Application as Catalyst in Catalytic Cracking of Heavy Fraction of Crude Oil - Is Fatimah; Karna Wijaya; Khoirul Himmi Setyawan (Bulletin of Chemical Reaction Engineering & Catalysis, 2008)
Research on synthesis and characterization of ZrO2-Montmorillonit and its application as catalyst in heavy fraction of crude oil (HFCO) conversion has been investigated. Synthesis of catalyst was done by pillarization of ZrO2 into silicate interlayer of montmorillonite structure. The success in synthesis is shown by XRD and BET surface area measurement in that basal spacing d001 was increase after pillarization. Activity test of material was showed that ZrO2 dispersion affected catalytic activity in liquid production and the activity was increased asn increasing temperature in the range of 473K-673K. Composition of liquid product indicated that ZrO2-Montmorillonit tend to produce kerosene related to metal oxide distribution in synthesis. © 2008 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)